2019
DOI: 10.1089/neu.2018.6332
|View full text |Cite
|
Sign up to set email alerts
|

Neuroectodermal Stem Cells Grafted into the Injured Spinal Cord Induce Both Axonal Regeneration and Morphological Restoration via Multiple Mechanisms

Abstract: Spinal cord contusion injury leads to severe loss of gray and white matter and subsequent deficit of motor and sensory functions below the lesion. In this study, we investigated whether application of murine clonal embryonic neuroectodermal stem cells can prevent the spinal cord secondary damage and induce functional recovery. Stem cells (NE-GFP-4C cell line) were grafted intraspinally or intravenously immediately or one week after thoracic spinal cord contusion injury. Control animals received cell culture me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Similarly to other studies, the intravenously administered cells did not settle in the organs due to the rapid cell clearance 27 , 37 . It could be argued that this controversy between the morphological and functional data may be partly due to the poor survival of human cells in immune-competent animals or a higher dose of hiPSCs is required to improve the tissue-sparing after SCI.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Similarly to other studies, the intravenously administered cells did not settle in the organs due to the rapid cell clearance 27 , 37 . It could be argued that this controversy between the morphological and functional data may be partly due to the poor survival of human cells in immune-competent animals or a higher dose of hiPSCs is required to improve the tissue-sparing after SCI.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, IL-10 treatment reportedly induces functional improvement following SCI, promotes neuronal survival and increases axon sparing 57 , 66 . The exact role of MIP1-alpha is not fully understood in the injured CNS, however, results from our laboratory earlier suggested that it may have a modulatory effect after SCI 26 , 27 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The combined application resulted in inflammation aggravation, macrophages cell infiltration, and chondroitin sulfate proteoglycans (CSPGs) increase at the transplant site, which reduced the transplanted cells’ survival rate [ 119 ]. In the experiment of Pajer et al, after implanting the human fibrin hydrogels carrying stem cells (NE-GFP-4C cell line), the disintegrated fibrin matrix induced stem cells’ death, which failed to improve the motor function and reduce the formation of glial [ 141 ]. Besides, the undesirable consequences of cell transplantation are noteworthy, such as allodynia caused by abnormal astrocyte differentiation [ 142 ], pain and spasm caused by the inappropriate functional connection of regenerative axons [ 143 ], tumors caused by excessive hyperplasia [ 133 ], abnormal activities and tissue compression caused by ectopic colonies [ 144 ], and others.…”
Section: Fibrin Hydrogels As a Cell Carriermentioning
confidence: 99%